International Electron Devices Meeting. IEDM Technical Digest
DOI: 10.1109/iedm.1997.650512
|View full text |Cite
|
Sign up to set email alerts
|

Channel engineering for the reduction of random-dopant-placement-induced threshold voltage fluctuation

Abstract: A simple model is proposed, which is able to calculate VTH standard deviation due to random dopant placement in the channel, for arbitrary vertical impurity distributions. Substantial decrease in VTH fluctuation, while keeping VTH the same, is confirmed for low surface impurity channel MOSFETs, in agreement with the model prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
1

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 4 publications
4
84
1
Order By: Relevance
“…When the channel length is scaled down to dimensions below 0.1 m, the doping concentration in the channel region has to be increased to levels above 1 10 cm . The results of our atomistic simulations show that the doping concentration dependence of the random dopant-induced threshold voltage fluctuations in sub-0.1-m MOSFET's with conventional architecture is stronger than the dependence suggested by most of the analytical models [3], [11], [15], [16]. Fig.…”
Section: Conventional Mosfet'smentioning
confidence: 90%
See 3 more Smart Citations
“…When the channel length is scaled down to dimensions below 0.1 m, the doping concentration in the channel region has to be increased to levels above 1 10 cm . The results of our atomistic simulations show that the doping concentration dependence of the random dopant-induced threshold voltage fluctuations in sub-0.1-m MOSFET's with conventional architecture is stronger than the dependence suggested by most of the analytical models [3], [11], [15], [16]. Fig.…”
Section: Conventional Mosfet'smentioning
confidence: 90%
“…Results of continuous-charge 3-D numerical simulations [9], [11] have shown that the introduction of a thin, low doped layer in the MOSFET channel, immediately below the interface, can efficiently suppress the threshold voltage fluctuations. This approach has been successfully demonstrated experimentally in MOSFET's with low doped epitaxial channels [15]. The introduction of a low doped region in the channel, however, makes the corresponding devices more susceptible to short channel effects.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…These architectures have additional benefits in terms of optimal threshold voltage control and improved mobility [19][20][21][22]. The undoped epitaxial layer thickness is restricted to approximately one-fifth of the effective channel length, due to short channel effects.…”
Section: Fluctuation Resistant Mosfet Architecturesmentioning
confidence: 99%